Securing the Automobile: the Next Steps - Pike, Lee; Sharp, Jamey; Tullsen, Mark; Hickey, Pat; Bielman, James (IEEE software, 2017)
Previous research has demonstrated the existence of pervasive softwarevulnerabilities that exist in modern automobiles. We present a rejoinder to thatwork here, discussing approaches to secure automotive software systems.